Developing interventions to address sexuality after stroke: Findings from a four-panel modified Delphi study - Margaret McGrath; Sandra Lever; Annie McCluskey; Emma Power (Medical Journals Sweden, 2019)
Background: Although stroke has a profound impact on sexuality there are limited evidence-based interventions to support rehabilitation professionals in this area. The aim of the current research was to prioritize content areas and approaches to sexual rehabilitation from the perspective of stroke survivors, their partners, stroke rehabilitation clinicians and researchers. Methods: A 2-step online Delphi method was used to prioritize the content of, and approaches to, sexual rehabilitation with stroke survivors, their partners, stroke rehabilitation clinicians and researchers. Results: Stroke survivors (n = 30), their partners (n = 18), clinicians and researchers in stroke rehabilitation (n = 45) completed at least 1 of 2 investigator-developed surveys. Participants prioritized 18 core content areas for inclusion in sexual rehabilitation following stroke with a high degree of consensus. Another 27 content areas were considered moderately important. There was strong consensus that sexual rehabilitation should be offered in the subacute and chronic phases of stroke recovery. Participants would prefer health professionals to deliver the intervention face-to-face. Conclusion: This study presents opinions from stroke survivors, partners of stroke survivors, clinicians and researchers. The information about content, timing and mode of delivery will be used to develop and evaluate a comprehensive sexuality rehabilitation programme.